Symmetric sodium-ion batteries—materials, mechanisms, and prospects. (October 2022) - Kumar, Ananya; Nagmani,; Puravankara, Sreeraj
Abstract: Sodium-ion batteries (SIBs) are an emerging and competing technology to Li-ion batteries for energy storage applications like low-consumption electronic devices, low-speed two and three-wheeler vehicles, and stationary storage. Symmetric battery configurations have drawn significant interest due to their low cost of materials, reduced volume expansion, and higher operational safety than their asymmetric counterparts. The symmetric electrode architecture makes it a more viable option with emerging battery configurations like a bipolar cell and is advantageous to the traditional unipolar structure. In non-aqueous Na-ion batteries, the more dense and cheaper Al brings cost-effectiveness to battery fabrication. For presenting materials perspective of symmetric electrodes in SIBs, we review transition metal-containing multiredox oxides and polyanionic compounds as bipolar materials for symmetric non-aqueous SIBs. The symmetric electrode materials' crystal structure and electrochemical performance are discussed, along with the perspectives for improving the energy density in designing new bipolar materials. The efficient recyclability of the electrode material and the substrate in a bipolar configuration provides a sustainable solution in SIBs for energy storage. Graphical abstract: Image 1 Highlights: Review of electrode materials, mechanisms, and prospects in symmetric sodium-ion batteries (SSIBs). Advantages of SSIBs in bipolar configuration. Design parameters and prospects for potential application of SSIBs. Insights for the choice of transition metal-ion for SSIB electrode materials. Cost-effectiveness, compensated volume expansion, improved safety, and ease of recyclability of symmetric electrode materials.